Variation in the Number and Position of rDNA Loci Contributes to the Diversification and Speciation in Nigella (Ranunculaceae) - Orooji, Fatemeh; Mirzaghaderi, Ghader; Kuo, Yi-Tzu; Fuchs, Jörg (Frontiers in Plant Science, 2022)
Nigella is a small genus belonging to the Ranunculaceae family which is presumably originated and distributed in Aegean and the adjacent Western-Irano-Turanian region. Comparative repeat analysis of N. sativa, N. damascena and N. bucharica was performed using low-pass Illumina genomic reads followed by karyotyping and FISH mapping of seven Nigella species using the in silico identified repeats and rDNA probes. High- and moderate-copy repeat sequences occupy 57.52%, 59.01% and 64.73% of N. sativa, N. damascena and N. bucharica genomes, respectively. Roughly, half of the genomes are retrotransposons (class I transposons), while DNA transposons (class II transposons) contributed to only about 2% of the genomes. The analyzed Nigella species possess large genomes of about 7.4 to 12.4 Gbp/1C. Only two satellite repeats in N. sativa, one in N. damascena and four in N. bucharica were identified, which were mostly (peri)centromeric and represented about 1% of each genome. A high variation in the number and position of 45S rDNA loci were found among Nigella species. Interestingly, in N. hispanica, each chromosome revealed at least one 45S rDNA site and one of them occurs in hemizygous condition. Based on the chromosome numbers, genome size and (peri)centromeric satellites, three karyotype groups were observed: Two with 2n = 2x = 12 and a karyotype formula of 10m + 2t (including N. sativa, N. arvensis, N. hispanica as the first group and N. damascena and N. orientalis as the second group) and a more distant group with 2n = 2x = 14 and a karyotype formula of 8m + 2st + 4t (including N. integrifolia and N. bucharica). These karyotype groups agreed with the phylogenetic analysis using ITS and rbcL sequences. We conclude that variation in (peri)centromeric sequences, number and localization of rDNA sites as well as chromosome number (dysploidy) are involved in the diversification of the genus Nigella.